Underwriter competition and gross spreads in the eurobond market - Michael G. Kollo (European Central Bank (ECB), 2005)
We investigate the competitive landscape of underwriting services in the Eurobond market including the choice of underwriter and underwriter gross spread. We find a significant but declining association between the home market of the Eurobond's currency of denomination and that of the lead underwriter. These bonds underwritten by underwriters `local' to the currency also carry significantly lower underwriter gross spreads vis-à-vis other Eurobonds. The amalgamation of the European currencies into the Euro resulted in a significant shift in the competitive landscape for underwriting services. We find a significant portion of market shares shifted from the `local' European underwriters to non-`local' U.S. underwriters with the introduction of the Euro. Moreover, the volume of new issues rose and the gross underwriter spread declined significantly. Our empirical results suggest that Eurozone underwriters responded to the increased entry of U.S. and other Eurozone underwriter with aggressive discounting of the underwriter gross spread.
Keywords: G15; G24; 330; Eurobond market; Underwriter competition; Underwriter spreads; Eurobond; Euromarkt; Börsengang; Internationaler Wettbewerb; EU-Staaten; USA